Comparison of Buccal Mucosal Epithelial Cell Analysis of Communities Around and Outside the Medan City Waste Landfill - T.Kemala Intan; Zulham Yamamoto; Causa Trisna Mariedina; Indryani Rachman; Matsumoto Toru (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: People living around waste final processing sites (TPAs) have the potential to experience chronic exposure to environmental pollution that can have an impact on health. Exposure to various pollutants from waste processing activities has the potential to cause cellular damage, including in buccal mucosal epithelial cells that can be used as biomarkers of cytogenetic damage. Objective: This study aims to examine the damage to buccal mucosal epithelial cells in people living around the Medan City Landfill and compare it with people who do not live in the area. Methods: This study used a cross-sectional design involving 100 respondents divided into two groups: the community living around the landfill (50 subjects) and the control group not living near the landfill (50 subjects). Buccal mucosal epithelial cells were collected using the cytobrush technique and stained using the Papanicolaou method. Analysis was carried out on the frequency of pyknosis, karyorrhexis, and karyolysis as cytogenetic biomarkers, with adjustment for potential confounders including sex, age, and duration of residence, then compared between the two groups. Results: The results showed that the frequency of buccal mucosal epithelial cells exhibiting pyknosis, karyorrhexis, and karyolysis in the community living around the landfill did not show a statistically significant difference compared to the control group (p > 0.05 for all cytogenetic endpoints). Conclusion: There was no significant difference in the frequency of cytogenetic endpoints (pyknosis, karyorrhexis, and karyolysis) of buccal mucosal epithelial cells between people living around the Medan City Landfill and those who did not. These findings indicate no evidence of significant genotoxicity based on the analyzed cytogenetic parameters in the studied population. However, continued environmental monitoring and longitudinal studies with larger sample sizes are recommended to detect subclinical cellular changes at earlier stages.